Influence of high-performance work system on employee service performance and OCB: The mediating role of resilience - Kashif Nadeem; Amir Riaz; Rizwan Qaisar Danish (Journal of Global Entrepreneurship Research, 2019)
Previous studies regarding high-performance work system (HPWS)-performance relationship have been conducted at organizational level of analysis, thus highlighted management perspective of this relationship. Furthermore, the widely acknowledged 'black-box' debate in this area invites researchers to identify and empirically test the mediating mechanism linking HPWS with performance outcomes. Using employee-level HPWS, this study proposed that HPWS is positively linked with employee service performance and their organizational citizenship behavior (OCB) and these direct relationships are mediated by employee resilience. Data were obtained from 371 front line employees working in service sector to test the proposed relationships. Findings of the study revealed that HPWS was positively linked with service performance and OCB. Further, employee resilience partially mediated both the direct relationships between HPWS and employee outcomes. Implications and limitations of the study were also discussed accordingly.
Keywords: 650; High performance work system (HPWS); Resilience; Employee service performance; Pakistan